Михаил Чайка-Чайковски (генерал Мехмед Садък паша) и българите в Тулчански санджак на Добруджа (40-70-те години на ХІХ в.) - Hadjynicolova, E. (Чорноморська минувшина, 2010)
Стаття Єлени Хаджиніколової написана болгарською мовою. В зв’язку з цим ми пропонуємо розгорнуте резюме українською мовою. Іn the article on the basis of analysis of periodic press of the ХІХ c. it is examined the M. Chaycovs’kyi’s connections with representatives of Bulgarian national revival, his attempt to solve the problems concerning the Church in Bulgaria, and general Mehmed Sadyk Pasha’s activity in Dobroudja.